Smooth zooming - Radan Šuba (A+BE: Architecture and the Built Environment, 2018)
Chapter 2 showed that current maps on the Internet are composed of the discrete set of LODs/scale pyramids with big changes of map content and representations. This can lead to confusion for the users when they navigate in the map. Therefore, a conceptual model (SSC) was proposed, see Chapter 3. We believe that, by capturing the whole generalization process in small smooth incremental changes, it is possible to achieve a better user experience e. g. when the user zooms in and out. To verify this hypothesis it is necessary: (1) generate a SSC dataset (2) develop a software prototype where a dataset can be used in its full potential and (3) perform usability test. Hence this chapter will describe the benefits of such as smooth representation in more detail. Section 6.1 gives an introduction to the problem and it suggests our solution. Section 6.2 covers the theoretical background, principle and example of smooth zooming. Section 6.3 presents possible conversion strategies to smooth representation. Section 6.4 explains the software prototype for possible usability testing. This is followed by our initial usability test, which was carry out addition to our plans. More specific, Section 6.5 defines all elements of the testing. Section 6.6 presents preliminary results, and Section 6.7 describes gained experiences. Then, Section 6.8 summarizes possible improvements for the future.